2004
DOI: 10.1002/ana.20225
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem pathology in DYT1 primary torsion dystonia

Abstract: DYT1 dystonia is a severe form of young-onset dystonia caused by a mutation in the gene that encodes for the protein torsinA, which is thought to play a role in protein transport and degradation. We describe, for the first time to our knowledge, perinuclear inclusion bodies in the midbrain reticular formation and periaqueductal gray in four clinically documented and genetically confirmed DYT1 patients but not in controls. The inclusions were located within cholinergic and other neurons in the pedunculopontine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 33 publications
4
127
3
3
Order By: Relevance
“…The formation of membranous whorls caused by expression of ⌬E-torsinA is evident in E-cadherin-positive and SH-SY5Y transfected cells (7,14) but has been also observed in other non-neuronal cell lines overexpressing ⌬E-torsinA (data not shown). These inclusions appear to originate from the NE (47) and have been detected in DYT1 brain, supporting a role in the pathogenesis of dystonia (15). Perinuclear inclusions have also been detected in mice expressing ⌬E-torsinA (48,49).…”
Section: Discussionmentioning
confidence: 73%
“…The formation of membranous whorls caused by expression of ⌬E-torsinA is evident in E-cadherin-positive and SH-SY5Y transfected cells (7,14) but has been also observed in other non-neuronal cell lines overexpressing ⌬E-torsinA (data not shown). These inclusions appear to originate from the NE (47) and have been detected in DYT1 brain, supporting a role in the pathogenesis of dystonia (15). Perinuclear inclusions have also been detected in mice expressing ⌬E-torsinA (48,49).…”
Section: Discussionmentioning
confidence: 73%
“…The lack of neuronal degeneration in torsion dystonia patients suggests the possibility of functional defects, possibly caused by subtle changes in connectivity such as those reported in sensorimotor cortex by diffusion tensor magnetic resonance imaging (Carbon et al, 2004). Though there is no evidence of neuronal degeneration, torsinA, laminA, and ubiquitin inclusions have been reported in midbrain of DYT1 patients (McNaught et al, 2004). Manifesting and non-manifesting carriers of DYT1 mutation show abnormal electrical excitability in the cerebral cortex and asymptomatic carriers of DYT1 mutation show altered resting glucose utilization and decreased D2 receptors in several brain areas as well as delayed motor learning (Eidelberg et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…The question of whether inclusion body pathology is specific to the transgenic mouse models, or whether it is also part of human DYT1 disease remains somewhat controversial. Most histopathological studies of brains from patients with DYT1 failed to find evidence of protein accumulation or inclusion bodies (Walker et al, 2002;Rostasy et al, 2003), but a recent study of postmortem material from DYT1 patients has reported that perinuclear inclusion bodies are present in neurons in various brain stem areas (McNaught et al, 2004).…”
Section: Animal Models For Dyt1 Dystoniamentioning
confidence: 99%